Regulatory of Nuclear Power Plant: Environmental Safety Aspect on Nuclear Power Plant Siting - Beta, Werdi Putra Daeng (Proceeding International Conference on Global Resource Conservation, 2013)
Nuclear Energy Regulatory Agency also called BAPETEN is a national regulatory authority for nuclear energy uses in Indonesia. Regulatory of Nuclear Power Plants (NPPs) is one of BAPETEN authorities for nuclear energy uses, including NPP siting. Regulatory of NPP consists of 5 (five) steps, there are siting, construction, commissioning, operation, and decommissioning. In This paper would be discussed regulatory of NPP siting, especially on environmental aspects. NPP site area is a geographical area that contains nuclear reactor, that is location in the land to be used for building, operation and decommissioning of one or more nuclear reactors for NPP facilities and all related systems, and within which the management of the authorized facility may directly initiate emergency actions. Site characteristics of NPP are very important to be considered in building and operating of NPP. One of some aspects to be considered is environmental safety of the site. This aspect should fulfill site criteria and requirement according to the regulation and reliable and in-depth studies, assessments related to environmental impact of nuclear reactors for power plants and the transfer of the released radioactive from nuclear reactor up to humans and the environment. Â Keyword: BAPETEN, environmental safety, NPP siteÂ